Decoding Split and Pool Combinatorial Libraries with Electron Transfer Dissociation Tandem Mass Spectrometry - Sarkar, Mohosin (J Am Soc Mass Spectrom, 2013)
Screening of bead-based split and pool combinatorial chemistry libraries is a powerful approach to aid the discovery of new chemical compounds able to interact with, and modulate the activities of, protein targets of interest. Split and pool synthesis provides for large and well diversified chemical libraries, in this case comprised of oligomers generated from a well-defined starting set. At the end of the synthesis, each bead in the library displays many copies of a unique oligomer sequence. Because the sequence of the oligomer is not known at the time of screening, methods for decoding of the sequence of each screening “hit” are essential. Here we describe an electron transfer dissociation (ETD) based tandem mass spectrometry approach for the decoding of mass-encoded split and pool libraries. We demonstrate that the newly described “chiral oligomers of pentenoic amides (COPAs)” yield non-sequence-specific product ions upon collisional activated dissociation; however, complete sequence information can be obtained with ETD. To aid in the decoding of libraries from MS and MS/MS data, we have incorporated (79)Br/(81)Br isotope “tags” to differentiate N- and C-terminal product ions. In addition, we have created “Hit-Find,” a software program that allows users to generate libraries in silico. The user can then search all possible members of the chemical library for those that fall within a user-defined mass error. [Image: see text]